Number of Pregnant Women at Four Dental Clinics and the Care They Received: A Dental Quality eMeasure Evaluation. Issue 10 (1st October 2019) - Neumann, Ana; Obadan‐Udoh, Enihomo; Bangar, Suhasini; Kumar, Shwetha V.; Tokede, Oluwabunmi; Kim, Aram; Yansane, Alfa; Mertz, Elizabeth; Panwar, Sapna; Gharpure, Arti; Kookal, Krisha Kumar; Mullins, Joanna; et al.
Abstract : Process‐of‐care quality measure research can be used to identify gaps in the delivery of dental services to pregnant patients. The aim of this study was to evaluate the types of dental services that pregnant patients received in four dental clinics over five years as documented in the electronic health record (EHR). To accomplish this objective, the authors modified and validated a previously published claims‐based dental quality measure for EHR use. After the electronic dental quality measure specifications were defined, the number of pregnant patients was calculated at three academic dental institutions and one large accountable care organization, and the types of dental care services they received over a five‐year period (2013‐17) were determined. Calibrated reviewers at each institution independently reviewed a sub‐sample of patient charts to validate the information obtained from EHR queries, and the concordance between manual chart reviews and EHR query reports was analyzed. Of the 335, 078 women aged 15‐44 years who received care at the four clinics for the five reporting years, 3.9% (n=13, 026) were pregnant. Among these pregnant patients, 48.9% (n=6, 366) received a periodic dental examination; 30.0% (n=3, 909) received a comprehensive dental exam; and 21.5% (n=2, 799) received additional dental services, irrespective of comprehensive or periodic oral evaluations. Overall, the mean proportion of pregnant patients seeking care in these academic dental and group practice clinics was low, but 78.9% of them received either a periodic or comprehensive oral evaluation. Given the importance of oral health care during pregnancy, these findings suggest a need for curriculum development to incorporate prenatal oral health education in the training of dental students.